Estrutura da assembleia de moluscos bentônicos da Plataforma Continental Oeste do Ceará, Brasil - Menezes, Renata Pereira (2020)
Mollusks have a wide variety of taxa and lifestyle habits. It is important to know its distribution and the species present throughout the coast of Brazil. The present work intends to show the structure of the assembly of benthic mollusks found in the western continental shelf of Ceará, in the region close to the counties of Itarema and Acaraú. The material was collected in February 2017, as na integral part of the Geodiversities, Interactions and Socioenvironmental Impacts Project in the Praia-Plataforma System on the West Coast of the State of Ceará, belonging to the Support Program for Centers of Excellence (PRONEX). Collection points were established and the material was collected with the aid of a Van Veen 3.5m³ sampler Each sample was initially screened by sifting through a 0.5 mm opening mesh, placed on labeled plastic pots and preserved in 70% ethyl alcohol, for further analysis in the laboratory. In the laboratory the material was washed in running water, sieved again in 0.5 mm mesh, stored in plastic pots and preserved in 70% ethyl alcohol. Subsequently, the samples were screened with the aid of a stereomicroscope and the specimens found were identified to the lowest possible taxonomic level, with the help of specialized bibliography. 72 different species were then identified, 51 of which were from the Gastropoda class, 16 from Bivalvia and five from Polyplacophora. 61 species were found on the continental shelf of Itarema, 46 from the Gastropoda class, 14 from the Bivalvia and one from Polyplacophora; and 20 species on the continental shelf os Acaraú, 13 from the Gastropoda class, 3 from the Bivalvia and 4 from the Polyplacophora. The malacofauna present in the collection points counted 375 individuals, being 330 from the Gastropoda class, 40 from Bivalvia and five from Polyplacophora. The species most found in Itarema was Alaba incerta, of the Gastropoda class, with a total of 99 individuals. And in Acaraú, the most found species was Eulithidium affine, of the Gatsropoda class, with a total of nine individuals. In Itarema, the points with the highest density of individuals were closest to the coast; while in Acaraú, the points of highest density were close to the outfall of Acaraú River. Species dominance was low while species diversity was high.